Resonance Properties in Auditory Brainstem Neurons - Fischer, Linda; Leibold, Christian; Felmy, Felix (Frontiers in Cellular Neuroscience, 2018)
Auditory signals carry relevant information on a large range of time scales from below milliseconds to several seconds. Different stages in the auditory brainstem are specialized to extract information in specific frequency domains. One biophysical mechanism to facilitate frequency specific processing are membrane potential resonances. Here, we provide data from four different brainstem nuclei that all exhibit high-frequency subthreshold membrane resonances that are all most likely based on low-threshold potassium currents. Fitting a linear model, we argue that, as long as neurons possess active subthreshold channels, the main determinant for their resonance behavior is the steady state membrane time constant. Tuning this leak conductance can shift membrane resonance frequencies over more than a magnitude and therefore provide a flexible mechanism to tune frequency-specific auditory processing.